2003
DOI: 10.3758/bf03196554
|View full text |Cite
|
Sign up to set email alerts
|

Grouping with and without attention

Abstract: The effects of perceptual grouping on a line discrimination task were investigated using Moore and Egeth's (1997) paradigm. Observers judged which of two lines, presented one above the other over a matrix of spots, was longer. On some trials, larger spots at both ends of the lines formed arrowheads, thereby making possible the Müller-Lyer illusion. When observers attended only to the lines, they were not aware of the arrowheads. Yet their line judgment performance showed that they had succumbed to the illusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
3
6
0
Order By: Relevance
“…Behavioral studies reported that grouping could influence visual performance even when observers are unaware of the presence of such grouping (26,28). Consistent with these observations, in our study, many of the observers reported after the experiment that they were unaware of the different kinds of groupings present among the shapes and that they simply ignored the background bars during the change-detection task.…”
Section: Methodssupporting
confidence: 79%
“…Behavioral studies reported that grouping could influence visual performance even when observers are unaware of the presence of such grouping (26,28). Consistent with these observations, in our study, many of the observers reported after the experiment that they were unaware of the different kinds of groupings present among the shapes and that they simply ignored the background bars during the change-detection task.…”
Section: Methodssupporting
confidence: 79%
“…Using this method, Moore and Egeth provided evidence that grouping occurs without attention and suggested that grouping failures reported in earlier studies may be due to failures of memory. Subsequent studies supported these findings (Chan & Chua, 2003; Russell & Driver, 2005; Lamy et al, 2006; Shomstein et al, 2010). …”
Section: Introductionmentioning
confidence: 73%
“…On some of the trials, the black dots were configured to induce a line length illusion in the case of grouping. Remarkably, the dots influenced the line length judgments, even though subjects could not report about the groupings when asked (see also Chan & Chua, 2003). Studies by Kimchi and Razpurker-Apfeld (2004) and Russell and Driver (2005) extended these findings.…”
Section: Previous Experiments On Perceptual Groupingmentioning
confidence: 99%